Memperkenalkan Psychogame© sebagai Media Literasi Kesehatan Mental Remaja - Karuniawaty, Titi Pambudi; Wiweko, Adnanto; Imaniaty, Nurul; Wiweko, Nadhira Asmazulfa (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Mental health problems in adolescents have become a crucial issue in recent times. Improving mental health literacy is an important strategy to prevent mental disorder in adolescents. Psychogame© has been developed as an educational tool about mental health. This serious game was received a positive feedback and good acceptance when it was introduced to a number of adolescents aged 11-15 years old in this community-based activity. Psychogame© are effectively used to improve knowledge, attitudes and behaviors related to mental health through an interesting and interactive approach. This innovative tool needs to be introduced more widely to adolescents in various backgrounds and age ranges as a mental health literacy medium.